Interfaith Interaction Framework In Comparative Religion Course At The Department Of Usuluddin - Tuan Syarifah Nursyaza Aina Tuan Mohd Zawawi; Aman Daima Md. Zain; Mohd Hasrul Shuhar; Mohd Safri Ali; Rahimah Embong; Hanif Md Lateh@Junid; Wan Mohd Fazrul Azdi Wan Razali (Human Resource Management Academic Research Society, 2024)
Volume: 9 No: 11 ( Page: 652 - 663)